Integrins identified as potential prognostic markers in osteosarcoma through multi-omics and multi-dataset analysis - Lei Cui; Shuai Zhao; Hai long Teng; Biao Yang; Qian Liu; An Qin (npj Precision Oncology)
Abstract Osteosarcoma represents 20% of primary malignant bone tumors globally. Assessing its prognosis is challenging due to the complex roles of integrins in tumor development and metastasis. This study utilized 209,268 osteosarcoma cells from the GEO database to identify integrin-associated genes using advanced analysis methods. A novel machine learning framework combining 10 algorithms was developed to construct an Integrin-related Signature (IRS), which demonstrated robust predictive power across multiple datasets. The IRS’s utility in predicting overall survival was confirmed using data from The Cancer Genome Atlas, underscoring its potential in personalized cancer management.